OPTIMASI PENYIMPANAN DAN PENCARIAN DATA PADA UMKM MELALUI ANALISIS DAN DBMS (STUDI KASUS : SEAFOOD TRUBUS TUBAN): OPTIMASI PENYIMPANAN DAN PENCARIAN DATA PADA UMKM MELALUI ANALISIS DAN DBMS (STUDI KASUS : SEAFOOD TRUBUS TUBAN) - amran, ali; Rohmah, Khoirur; Dewi, Herdiyanti Kusuma` (Curtina, 2024)
Database management system (DBMS) are key technology and can provide great benefits for MSMEs. DBMS allows MSMEs to manage storage, customer, inventory and transaction data more efficiently. DBMS provides a structured and organized storage mechanism, DBMS helps manage and access information that is important for daily operations. Apart from that, DBMS also provides data reliability and security which increases the integrity of business information. Furthermore, a DBMS facilitates better data analysis for its use, by storing historical data and allowing for easier and more efficient data extraction and analysis. DBMS can help MSMEs to make decisions based on identified facts and trends. In addition, DBMS supports integrity with other applications, such as online payment systems, digital marketing, supply chain management, which increases the effectiveness and competitiveness of MSMEs in an increasingly digitally connected market . In today’s digital context the use of DBMS solutions provides an important competitive advantage for MSMEs. However, challenges related to cost and the need for technical expertise remain considerations. In conclusion, the use of DBMS in MSMEs plays a vital role in supporting efficiency, analysis and data security which are key factors for business success and growth.